Հայկական միջնադարյան զարդարվեստը որպես ազգային տեքստիլ տեխնոլոգիաների ամրագրման միջոց - Սոֆյա Գալֆայան; Լուսինե Մխիթարյան (ՀՀ ԳԱԱ հրատ.)
В работе выдвигается гипотеза, что рисунки, создаваемые ходом ниток в плетеных и узелковых элементах, получаемых в результате технологических решений армянского рукодельного текстиля, возможно, представляют собой определенные идеограммы, передаваемые из поколения в поколение.In our work we have pulled forward the hypothesis that pictures created by the run of thread in weaven and knot-made elements in the result of technological solutions of Armenian handmade textile probably have some ideographical meaning, and passing them from generation to generation has once been of great importance.
Keywords: N Fine Arts; Technology; Handicrafts; Arts and crafts; NX Arts; Textile Industries